El bullying y su influencia en el aprendizaje de los estudiantes de octavo año de EGB de la Unidad Educativa Adolfo María Astudillo periodo 2022-2023 - Asanza Vergara, Angie Nicole (2023)
In this case study, it is revealed what bullying is, how it influences students, and the problems that exist in the educational unit ´´Adolfo María Astudillo´´ are detailed, the characteristics of bullying, and the causes that They cause bullying in educational units. The symptoms that the student may present at home are also described, in order to identify that they are suffering from bullying at school. On the other hand, it is important to know how to prevent this type of harassment within educational units, since it is essential to prevent these cases in schools, so that they do not become more serious problems later. Another point detailed in this research is how teachers and parents should act in cases of harassment, what factors should be taken into account at home, and in educational units, in order to guarantee well-being. of the students